The Relationships of Future Anxiety with some Variables among the Vocational Training Students - Zegaoua Ahmed (Sultan Qaboos University, 2013)
The Purpose of this study was to investigate the level of future anxiety among students of' vocational training. The relationship of future anxiety gender and vocational specialization was tested. The researcher developed a questionnaire of future anxiety which was distributed to 112 students who were in four vocational specializations. The results revealed that there was an average level of future anxiety among the vocational training students, in the total score as well as in the vocational, academic, social, and psychological dimensions. However, there was low level of future anxiety in the economic dimension. There were also statistically significant differences between males and females on the level of future anxiety, while there were no statistically significant differences on the other dimensions attributed to the vocational specialization. In light of the findings the researcher proposed a number of recommendations.